2017
DOI: 10.1164/rccm.201603-0523oc
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response and Mortality Risk Relate to Distinct Lung Microbiomes in Patients with HIV and Pneumonia

Abstract: These data provide evidence that compositionally and structurally distinct lower airway microbiomes are associated with discrete local host immune responses, peripheral metabolic reprogramming, and different rates of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 40 publications
1
68
1
Order By: Relevance
“…Lower airway microbial metagenomic functional capacity correlates with circulating metabolites and mortality in HIV-infected patients with pneumonia (Shenoy et al, 2016), providing evidence that active microbial metabolism affects the outcome of immune-compromised host. Paradoxically, genes encoding metabolic pathways for both propionate and butyrate were decreased in subjects with detectable propionate and butyrate.…”
Section: Discussionmentioning
confidence: 99%
“…Lower airway microbial metagenomic functional capacity correlates with circulating metabolites and mortality in HIV-infected patients with pneumonia (Shenoy et al, 2016), providing evidence that active microbial metabolism affects the outcome of immune-compromised host. Paradoxically, genes encoding metabolic pathways for both propionate and butyrate were decreased in subjects with detectable propionate and butyrate.…”
Section: Discussionmentioning
confidence: 99%
“…The study also noted that specific metabolic features, including products of vitamin E, fatty acid, and arginine metabolism, were related to peripheral CD4 1 cell counts (28). More recently, using a cohort of 182 HIV-infected patients with pneumonia, Shenoy and colleagues demonstrated the existence of three compositionally distinct airway bacterial microbiota, each predicted to encode metagenomes capable of producing the metabolites detected in paired serum samples from these microbiologically stratified patient groups (29). Each pathogenic microbiota state induced a specific host immune response.…”
Section: Mechanisms Of Host Response and Diseasementioning
confidence: 94%
“…This was demonstrated in a study of lean and obese individuals who were better differentiated by their gut metagenome as opposed to their microbiota profile . Finally, recent biomarker sequencing studies of large patient cohorts have demonstrated that several distinct microbiota conformations are evident in patients with a given clinical indication and are related to differences in immunologic profiles and clinical features of disease . This implies that within a given diseased patient population several pathogenic microbiomes may exist; however, such possibilities remain unexplored in the field of NAFLD microbiome research.…”
Section: The Gut Microbiome In Nafldmentioning
confidence: 99%